The G60S connexin 43 mutation activates the osteoblast lineage and results in a resorption‐stimulating bone matrix and abrogation of old‐age–related bone loss. (18th October 2013) - Zappitelli, Tanya; Chen, Frieda; Moreno, Luisa; Zirngibl, Ralph A; Grynpas, Marc; Henderson, Janet E; Aubin, Jane E
ABSTRACT We previously isolated a low bone mass mouse, Gja1Jrt/ + , with a mutation in the gap junction protein, alpha 1 gene (Gja1), encoding for a dominant negative G60S Connexin 43 (Cx43) mutant protein. Similar to other Cx43 mutant mouse models described, including a global Cx43 deletion, four skeletal cell conditional‐deletion mutants, and a Cx43 missense mutant (G138R/ +), a reduction in Cx43 gap junction formation and/or function resulted in mice with early onset osteopenia. In contrast to other Cx43 mutants, however, we found that Gja1Jrt/+ mice have both higher bone marrow stromal osteoprogenitor numbers and increased appendicular skeleton osteoblast activity, leading to cell autonomous upregulation of both matrix bone sialoprotein (BSP) and membrane‐bound receptor activator of nuclear factor‐κB ligand (mbRANKL). In younger Gja1Jrt/+ mice, these contributed to increased osteoclast number and activity resulting in early onset osteopenia. In older animals, however, this effect was abrogated by increased osteoprotegerin (OPG) levels and serum alkaline phosphatase (ALP) so that differences in mutant and wild‐type (WT) bone parameters and mechanical properties lessened or disappeared with age. Our study is the first to describe a Cx43 mutation in which osteopenia is caused by increased rather than decreased osteoblast function and where activation of osteoclasts occurs not only through increased mbRANKL but an increase in a matrix protein that affects bone resorption, which together abrogate age‐related bone loss in older animals. © 2013 American Society for Bone and Mineral Research.